(untitled) (Scientific journal of the Fergana State University, 2024)
In this article we will look at the pedagogical challenges that teachers and educators face when developing research skills among the younger generation in Uzbekistan. We will also discuss possible solutions to these problems and ways to promote the development of a culture of inquiry among future teachers. The formation of a teacher’s research competence requires changing the nature and content of the technology of pedagogical education. We are talking about teaching a new intellectual vision, including the style of scientific thinking, the main indicators of which are discreteness, continuity, staticity, and syntheticity. Scientific thinking is also characterized by systematicity, dynamism, problematicity, categoricality, reflexivity, evidence, predictability, projectivity, search, creativity, etc. [1]. These thinking features are, in our opinion, the most important indicators of the “quality” of a teacher’s research competence. Modeling the process of developing research competence is a specific way of cognition, in which the object of research is the process of developing research competence. We are talking about research skills, including the ability to pose questions, analyze information, develop hypotheses, conduct experiments and interpret results, which are the foundation for any professional activity and, of course, in the development of research competence in future teachers.